A study on the thickening time of class F fly ash geopolymer cement for oil well cementing - Kanesan, D. (Asian Research Publishing Network, 2018)
With the increasing awareness towards global warming, there is a dire need to develop a green cement to replace the conventional Ordinary Portland Cement (OPC). Geopolymer cement has been identified as a potential replacement for the OPC and its suitability for oil well cementing applications are being studied extensively. The determination of thickening time is crucial for oil well cementing to avoid catastrophic incidents due to premature cement setting. This research investigates the thickening time of class F fly ash based geopolymer cement at different densities (low, medium and high) according to the industrial standards with and without the addition of retarders. Three formulations with different ratios of Sodium Hydroxide (NaOH) to Sodium Silicate (Na2SiO3), molarity of NaOH, Fly Ash to Alkali ratio, and water content were used to come up with cement densities of 11ppg, 15ppg and 17ppg. The thickening time was determined using a High Pressure High Temperature (HPHT) consistometer at pressure and temperature of 2000 psi and 60 oC respectively. The results shows that the medium density formulation of fly ash geopolymer cement resulted in the longest duration of thickening time compared to the low and high density formulations. In addition, it was found that addition of retarder contributed to less than 10 of the increment in thickening time for all three cement densities. Â© 2006-2018 Asian Research Publishing Network (ARPN).